Large area gridded field emitter arrays using anodised aluminium - Holland, E; Li, Y; Abbott, P; Wilshaw, P (Elsevier, 2000)
We report a novel non-lithographic technique to produce gridded field emitter arrays. Porous anodic alumin membranes with well-defined pores (approximate to 160 nm) and high pore density have been exploited to fabricate a very high density of filed emitters (approximate to 55 x 10(8) cm(-2)). An additional advantage is offered by the small size of the individual emitter devices (approximate to 160 nm grid aperture), allowing operation with only moderate extraction voltages. The lowest extraction voltage at which emission was observed (0.1 nA) was 15 V. Arrays containing approximately 200,000 emitters have shown that emission current densities of up to 30 mA cm(-2) (50 V extraction voltage) can be achieved. Recent results have shown a performance suitable for display devices and this technique is a potential route for the development of large, inexpensive displays. (C) 2000 Elsevier Science B.V. All rights reserved.